SOCIAL VALUES REFLECTION EFFECT OF STUDENTS CONDUCT PRACTICE MOTOR ACTIVITIES - Ionescu C.L (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2013)
Physical education in the context of higher education is a key factor for the formation of future citizens in terms of personality training, by developing and promoting a list of values, behavior and social and personal attitudes manifested in everyday life. Characteristic notes of this stage, I defined here the student life, become evident through constant affirmation of consciousness, awareness of assuming the roles and responsibilities through challenges imposed by significant changes, objective and subjective, joined to maturation of social cognitive, mental, physical processes necessary to discovery and efficiency of social-relational and professional dimensions. The social integration of young people in social actual assembly is carried out and manifests through materialization of personal efforts in various media represented by family, group (membership, reference), and the working environment by positive modeling of personality, as well as by manifestation of personal autonomy. The concern of young people, especially the students, for the idea of physical movement designed in various forms, are reflected in their willingness to engage in physical education and sports activities as an alternative to a series of adverse events that have an impact on health and are evident in the society in which we live. Even if the physical education and sport is acknowledged to be particularly practical, it may be considered by the human resource involved in this process by promoting the practice of motor activity, the promoter for the formation and manifestation of behavior and positive attitudes for exercise for the promotion and development of value sets according to society's actual needs [1]. Corresponding to the highlighted above I have completed a scientific investigation included in the doctoral thesis [1], which presents an approach to physical education and sport field in terms of awareness of social values assimilation through the physical education. The research methods used were the focus group, sociometric questionnaire, simulation, questionnaire of values, opinions and attitudes and the method of processing and statistical analysis, charting, analysis tools and statistical indicators.